Microdosimetric characterization of clinical carbon‐ion beams using synthetic diamond detectors and spectral conversion methods. Issue 2 (4th December 2019) - Magrin, Giulio; Verona, Claudio; Ciocca, Mario; Marinelli, Marco; Mastella, Edoardo; Stock, Marcus; Verona‐Rinati, Gianluca
Abstract : Purpose: To investigate for the first time the potentialities of obtaining microdosimetric measurements in scanned clinical carbon‐ion beams using synthetic single crystal diamond detector and to verify the spectral conversion methods. Methods: Microdosimetric measurements were performed at different depths in a water phantom at the therapeutic scanned carbon‐ion beam of the National Center of Oncological Hadrontherapy (CNAO) in Pavia, using waterproof encapsulated diamond microdosimeter developed at "Tor Vergata" University. A monoenergetic carbon‐ion beam of 195 MeV/μ scanned over a square field of 2 × 2 cm 2 was used. Experimental microdosimetric spectra were compared with those obtained with a propane‐filled Tissue Equivalent Proportional Counters (TEPCs) microdosimeter in the same facility at the same conditions. To this purpose, the spectra in diamond were converted to the spectra that would have been collected with a propane‐filled cylindrical sensitive volume by means of a novel analytic methodology, recently developed at MedAustron. Results: The microdosimetric spectra acquired by the diamond microdosimeter show different shapes in the 10 keV µm −1  ÷ 10 3  keV µm −1 lineal‐energy range at different water depths. In spite of the high counting rate, no spectral distortion, due to pile‐up events and polarization effects, were observed. The experimental spectra have a low detection threshold of about 6 keV µm −1 due to the electronic noise in the irradiation room. The comparison between the spectra converted to propane from diamond detector and the spectra collected directly with propane‐filled TEPC shows a good agreement in the whole lineal‐energy range. Furthermore this comparison confirms that diamond detector response is LET independent. The frequency‐ and dose‐mean lineal energy values were also assessed for all spectra. The frequency‐mean values obtained with diamond microdosimeter at different depths scales rather well with the absorbed dose values. Conclusions: Microdosimetric characterization of a synthetic single crystal diamond detector in high‐energy scanned carbon‐ion beams was performed. The results of the present study showed that this detector is suitable for microdosimetry of clinical carbon ion beams. In addition, the good agreement between the converted diamond spectra and those obtained with TEPC provides the first experimental validation of the spectra conversion methodologies as valuable tools for the comparison of spectra collected with different detectors. Abstract :